Lord Byron and the Empress Marie-Louise: A New Letter to Leigh Hunt. Issue 2 (December 2017) - Steier, Michael P.
Abstract : This essay prints a new Byron letter to Leigh Hunt from late April of 1814. The previously unnoticed letter, which fills a significant gap in a sequence of letters that were exchanged between the two friends during the month of Napoleon's abdication, contains one of Byron's earliest recorded opinions of the French Emperor's second wife, the Austrian-born Marie-Louise. Byron's letter first appeared in the 1 May 1814 issue of Hunt's Examiner and is here reproduced from that text with commentary.